Anemia and cancer - Dwilewicz-Trojaczek, Jadwiga (Contemporary Oncology/Współczesna Onkologia, 2004)
Both cancers and haematopoietic neoplasms may be accompanied by anemia of various intensity. Anemia may cause a wide range of symptoms and impairments in almost every organ and tissue of the human body. The severity of these symptoms depends on the degree of anemia. The degree of anemia may be scaled as mild, moderate and severe. One of the frequent causes is the anemia of chronic disorders (ACD) caused by iron reutilization defect, iron stores are adequate or increased, but serum iron and iron binding capacity is low, and serum ferritin is normal or elevated. There is a relative lack of erythropoietin and erythropoiesis impairment. Moreover, the anemia in cancer patients may be caused by the shortening of erythrocyte life expectancy (due to autoimmunization, hypersplenism or microangiopathic anemia); the lack of haematopoietic factors (iron, folic acid, vitamin B12); bone marrow cancerous infiltration; fibromatosis or bone marrow stroma necrosis; chemo- or radiotherapy may also add to the anemia growth. Anemia worsens oxygen saturation of crucial organs. It is one of the most important reasons of tumor hypoxia, which stimulates the disease development and worsens the radio- and chemotherapy response. Anemia impairs living conditions of patients. Anemia treatment depends on the mechanism which leads to its development. In ACD, the best results are achieved when recombined erythropoietin is employed. In auto-immune-hemolytic anemia there are indications for immunosuppressive treatment, whereas hypersplenism is an indication for splenectomy.